An Ethnographic Study on the Opportunity and Challenges Faced by the Sikamī (Woodcarvers) of Bhaktapur Municipality in Woodcarving - Gosai, Saroj Raj (Bagiswori Journal, 2025)
This study explores the opportunities and challenges faced by Sikamī (Shilpakars) of Bhaktapur Municipality, the woodcarving artisans and entrepreneurs, with a focus on preserving and promoting this heritage craft over the past four decades. It is qualitative research with ethnographic method applying interpretive paradigm. Field observations, document analysis and interviews were employed in the research. The findings of the research reinforce that the revival of traditional architectural designs and the restoration of ancient monuments have significantly boosted the demand for traditional woodcarvings. Initiatives of the local government, including training programs for individuals from diverse caste groups, have broadened participation in this craft, fostering its independent practice. The expansion of the tourism industry has further widened the market, enhancing production to meet growing demand. Notably, the inclusion of women in woodcarving indicates a progressive shift, contributing to the industry’s sustainability. However, challenges such as the disinterest of younger generations, particularly among traditional Sikamī families, and the impact of modern technology on traditional skills threaten the craft’s continuity. The study emphasizes the need to honor and support traditional artisans as custodians of cultural heritage, ensuring the preservation and evolution of this vital art form. The study provides insights into how globalization and technological changes impact local crafts. It can help Sikamī adapt to changing market demands along with preservation of traditional skills, heritage conservation, develop tourism industry.